Adsorption of Aniline from Aqueous Solution Using Copper-Exchanged ZSM-5 and Unmodified H-ZSM-5 - J. O'Brien; T. Curtin; T.F. O'Dwyer (Adsorption Science & Technology)
Three medium-pore aluminosilicates were investigated with a view to examining their potential as adsorbents for the removal of aniline from aqueous solutions. H-ZSM-5 was exchanged with copper to prepare two different metal-loaded zeolites. The aqueous stability of the copper-exchanged zeolites was then examined by assessing the quantity of copper leached from each zeolite into solution as a function of pH. The optimum stability range with minimal copper leaching occurred between pH values of 5 and 9. The adsorption of aniline from aqueous solution onto each of the three zeolites was carried out within this pH window and the influence of the exchanged copper on the uptake level was assessed. The sorption experiments indicated an uptake level of approximately 40 mg/g for each zeolite. In all cases, the process followed the Langmuir adsorption model with the level of aniline adsorbed being largely unaffected by a change in temperature or the presence of extra-framework copper.